Saga (2012), volume 8 ebook - Vaughan, Brian K. (Saga (2012), 2017)
After the traumatic events of the War for Phang, Hazel, her parents, and their surviving companions embark on a life-changing adventure at the westernmost edge of the universe. Collects SAGA #43-48. Author: Brian K. Vaughan. Illustrator: Fiona Staples . 2017 Brian K. Vaughan & Fiona Staples.